2013
DOI: 10.1111/ajt.12383
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Adult Dual Kidney Transplants by KDRI in the United States

Abstract: UNOS guidelines provide inadequate discriminatory criteria for kidneys that should be transplanted as single (SKT) versus dual (DKT). We evaluated the utility of the kidney donor risk index (KDRI) to define kidneys with better outcomes when transplanted as dual. Using SRTR data from 1995 to 2010 of de novo KTX recipients of adult deceased-donor kidneys, we examined outcomes of SKT and DKT stratified by KDRI group 1.4 (n ¼ 49 294), 1.41-1.8 (n ¼ 15 674), 1.81-2.2 (n ¼ 6523) and >2.2 (n ¼ 2791). DKT of kidneys w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…They urged a more aggressive and consistent approach to the use of DKT. More recently, Klair et al (31) analyzed the UNOS database from 1995 to 2010 and found better graft survival for DKT for organs with KDRI >2.2, suggesting that the utilization of these marginal organs as dual organs should be considered for certain recipient categories to improve outcomes and resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…They urged a more aggressive and consistent approach to the use of DKT. More recently, Klair et al (31) analyzed the UNOS database from 1995 to 2010 and found better graft survival for DKT for organs with KDRI >2.2, suggesting that the utilization of these marginal organs as dual organs should be considered for certain recipient categories to improve outcomes and resource utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, even the recipients of kidneys with KDPI > 85% were at a much lower risk of death 2 years after transplant compared to those remaining on dialysis waiting for low-KDPI kidneys [13]. Moreover, such ECDs could be considered for the double kidney transplantation to a single recipient that provide better patient and graft survival in comparison to transplantation of such kidneys to 2 recipients [14, 15], and the use of the additional pre-transplant donor biopsy morphology score [16] secures the kidney transplantation from a high KDPI donor that otherwise may be discarded [17-20] and helps to allocate a donor organ to single or double transplantation. The results of the aforementioned studies highlight the important limitation of the current version of KDPI that could overestimate the prognostic weight of age based on the generalization from the total deceased donor population, and do not assume the specific constellation of parameters of a given donor.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore one must be cautious while taking decision on the basis of KDPI. However, Klair et al used KDRI for DKT and concluded that KDRI > 2.2 is a useful discriminatory cut-off for the determination of graft survival [28]. …”
Section: Criteria For Selection Of Donormentioning
confidence: 99%
“…If e GFR is greater than 60 ml/minute or KDRI is less than 2.2 then kidneys should go for SKT [24, 28]. If e GFR is less than 60 ml/minute or KDRI is greater than 2.2 then these patients should undergo biopsy to decide for SKT versus DKT.…”
Section: Criteria For Selection Of Donormentioning
confidence: 99%
See 1 more Smart Citation